2021
DOI: 10.1093/ajcp/aqab036
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Nodal Metastasis Detection in Endometrial Carcinoma With Microcystic, Elongated, and Fragmented (MELF) Pattern by Cytokeratin Immunostaining

Abstract: Objectives The microcystic, elongated, and fragmented (MELF) pattern of myoinvasion in endometrial carcinoma (EC) is associated with an increased risk of lymph node metastasis. Our aim is to assess the role of cytokeratin immunohistochemical (IHC) stains in detecting sentinel nodal metastasis in MELF pattern tumors. Methods We recovered 19 MELF pattern EC hysterectomies with lymphadenectomy from our files. Negative nodes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Often subtle nodal metastases occurring in MELF-type ECs may also be precisely recognized with CK19 immunostaining [80,82]. Recently, Rabe et al [83] suggested the routine CKs staining on sentinel lymph nodes in MELF-pattern ECs to detect metastases and isolated tumor cells. Similarly, another study demonstrated that staining with CK8 and CK18 may be useful in detecting LVSI, emphasizing that higher stages of ECs had statistically higher LVSI (p ≤ 0.005) [66].…”
Section: Prognostic Significance and Relation With Clinicopathologica...mentioning
confidence: 99%
“…Often subtle nodal metastases occurring in MELF-type ECs may also be precisely recognized with CK19 immunostaining [80,82]. Recently, Rabe et al [83] suggested the routine CKs staining on sentinel lymph nodes in MELF-pattern ECs to detect metastases and isolated tumor cells. Similarly, another study demonstrated that staining with CK8 and CK18 may be useful in detecting LVSI, emphasizing that higher stages of ECs had statistically higher LVSI (p ≤ 0.005) [66].…”
Section: Prognostic Significance and Relation With Clinicopathologica...mentioning
confidence: 99%
“…Moreover, Tahara et al 3 reported a strong expression of programed death-ligand 1 (PD-L1) in the invasive front of the MELF pattern and concluded that programed cell death protein 1/PD-L1 immunotherapy demonstrated significant therapeutic effect on the management of patients with endometrial cancer and grade 1 MELF. Furthermore, Rabe et al 4 claimed that cytokeratin IHC staining could detect malignant cells in the sentinel lymph nodes of patients with endometrial cancer and MELF.…”
mentioning
confidence: 99%